2020
DOI: 10.1097/md.0000000000021329
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy efficacy after first-line immunotherapy in 18 advanced melanoma patients

Abstract: In BRAF wild type advanced melanoma, immune checkpoint blockers such as anti-PD1 (anti-programmed cell death 1) are usually continued beyond progression for a hypothetical rare further response. Chemotherapy as a second-line option is considered ineffective by many practitioners based on historical data. Continuing anti-PD1 beyond progression has a high health-economic impact and is not recommended by the FDA. This study aimed to describe the efficacy and survival of advanced melanoma pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
7

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 22 publications
1
15
0
7
Order By: Relevance
“…Our results are in accordance with articles published by Karachaliou et al, 45 Goldinger et al 46 Weber et al 47 and Ribas et al 5 but differ from those by Hadash et al , St Jean et al and Markovi et al 32,33,37 whose studies showed improved outcomes for patients treated by CC after ICI than patients treated by CC who were not previously treated by ICI. Additionally a retrospective study also suggested an improved clinical outcome in seven patients treated by carboplatin and paclitaxel after progression on ICI 36 which suggests that the synergistic effect of ICI may be dependent of the type of CC used.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are in accordance with articles published by Karachaliou et al, 45 Goldinger et al 46 Weber et al 47 and Ribas et al 5 but differ from those by Hadash et al , St Jean et al and Markovi et al 32,33,37 whose studies showed improved outcomes for patients treated by CC after ICI than patients treated by CC who were not previously treated by ICI. Additionally a retrospective study also suggested an improved clinical outcome in seven patients treated by carboplatin and paclitaxel after progression on ICI 36 which suggests that the synergistic effect of ICI may be dependent of the type of CC used.…”
Section: Discussionsupporting
confidence: 91%
“…Published studies in non‐small cell lung cancer (NSCLC) and in other solid cancer types suggest that a prior treatment by immunotherapy may increase response to CC 23–31 . Several studies have also suggested this in melanoma, where it has been shown that a prior treatment by immunotherapy may improve response to CC by increasing the number of cytotoxic T cells in the peripheral blood in patients treated by CC, but these results have been challenged by other studies that have not reported better clinical outcomes in patients treated by CC after immunotherapy failure 32–37 …”
Section: Introductionmentioning
confidence: 99%
“…This single‐centre retrospective study found that CP therapy for nivolumab‐resistant ALM and MCM conferred greater RR, OS and PFS than ipilimumab. Although the RR of conventional chemotherapy as the first‐line treatment has been reported to be 5–12% in large‐scale studies, 5 three other case series have reported the RR of chemotherapy after IO drugs for melanoma to be 5·4%, 16·7% and 28·6%, respectively 2–4 . However, the survival benefits of the three previous studies were unclear owing to the short observation period and lack of a control group.…”
Section: Group Ni Ipi Cpmentioning
confidence: 99%
“…Although the RR of conventional chemotherapy as the first-line treatment has been reported to be 5-12% in large-scale studies, 5 three other case series have reported the RR of chemotherapy after IO drugs for melanoma to be 5Á4%, 16Á7% and 28Á6%, respectively. [2][3][4] However, the survival benefits of the three previous studies were unclear owing to the short observation period and lack of a control group. This and previous studies seem to support the hypothesis that certain chemotherapy regimens may promote tumour immunity.…”
mentioning
confidence: 99%
“…Subsequently, ipilimumab, the Cytotoxic T-Lymphocyte Antigen 4 (CTLA-4) blocking monoclonal antibody and BRAF V600E kinase inhibitor vemurafenib have been approved by the Food and Drug Administration (FDA). In combination, these therapies can somewhat improve outcomes and 5-year SR but are often also accompanied by gastrointestinal, endocrine, and immune overreaction and other adverse reactions [ 19 ].…”
Section: Introductionmentioning
confidence: 99%